THE USE OF INSTAGRAM IN TEACHING WRITING DESCRIPTIVE TEXT: A CASE STUDY IN AN INDONESAIAN PRIVATE SENIOR HIGH SCHOOL - Nurtajali Nurtajali; Iin Inawati; Ani Susanti (PROJECT (Professional Journal of English Education), 2023)
Teaching writing can be both challenging and fun. Using Instagram as a medium for descriptive writing makes it easier for teachers to create engaging learning experiences. This convenience helps teachers achieve their learning goals in the classroom. The aims of the study were to investigate the teachers strategy in teaching descriptive text using Instagram, analyze the students’ descriptive text produced by the students when the teaching strategy is implemented, and find out the students' response toward the teachers strategy in teaching descriptive text using Instagram. Researchers conducted qualitative research using a case study design. Two English teachers and 25 students from SMATQ Taman Cinta Al-Qur’an Barito Kuala, South Kalimantan, participated in the study. Data were collected using semi-structured interviews, classroom observations, and documentation.The findings reveal that teachers used sensory strategies, figurative language, and vivid words to teach descriptive text through three processes: pre-teaching, while-teaching, and post-teaching. Resulting in increased enthusiasm and motivation among students. Assessments showed a significant improvement in average scores, from 70 to 80. Students also enjoyed writing descriptive texts and found Instagram to be an appealing platform for learning, as it increased self-confidence and made ideas more cohesive.